When and how are lies told? And the role of culture and intentions in intelligence-gathering interviews - Deeb, Haneen (Legal and criminological psychology, 2020)
PURPOSE-Lie-tellers tend to tell embedded lies within interviews. In the context of intelligence-gathering interviews, human sources may disclose information about multiple events, some of which may be false. In two studies, we examined when lie-tellers from low- and high-context cultures start reporting false events in interviews and to what extent they provide a similar amount of detail for the false and truthful events. Study 1 focused on lie-tellers' intentions, and Study 2 focused on their actual responses.METHODS-Participants were asked to think of one false event and three truthful events. Study 1 (N = 100) was an online study in which participants responded to a questionnaire about where they would position the false event when interviewed and they rated the amount of detail they would provide for the events. Study 2 (N = 126) was an experimental study that involved interviewing participants about the events.RESULTS-Although there was no clear preference for lie position, participants seemed to report the false event at the end rather than at the beginning of the interview. Also, participants provided a similar amount of detail across events. Results on intentions (Study 1) partially overlapped with results on actual responses (Study 2). No differences emerged between low- and high-context cultures.CONCLUSIONS-This research is a first step towards understanding verbal cues that assist investigative practitioners in saving their cognitive and time resources when detecting deception regardless of interviewees' cultural background. More research on similar cues is encouraged.